Progressive chromatin rewiring by ETO2::GLIS2 revealed in a genome-edited human iPSC model of pediatric leukemia initiation - Boudia, Fabien; Baille, Marie; Babin, Loélia; Aid, Zakia; Robert, Elie; Rivière, Julie; Galant, Klaudia; Alonso-Pérez, Verónica; Anselmi, Laura; Arkoun, Brahim; Abermil, Nassera; Marzac, Christophe; et al. (Blood, 2025)
•Precise engineering of the ETO2::GLIS2 fusion in iPSC reproduces leukemogenesis in a developmentally relevant human cell context.•The osteoblastic homeobox DLX3 is essential for ETO2::GLIS2 leukemia initiation from iPSC and imbalanced activities at ETS and GATA motifs. [Display omitted] Pediatric acute myeloid leukemia frequently harbors fusion oncogenes associated with poor prognosis, including KMT2A, NUP98, and GLIS2 rearrangements. Although murine models have demonstrated their leukemogenic activities, the steps from a normal human cell to leukemic blasts remain unclear. Here, we precisely reproduced the inversion of chromosome 16 resulting in the ETO2::GLIS2 fusion in human induced pluripotent stem cells (iPSCs). iPSC-derived ETO2::GLIS2-expressing hematopoietic cells showed differentiation alterations in vitro and efficiently induced in vivo development of leukemia that closely phenocopied human acute megakaryoblastic leukemia (AMKL), reflected by flow cytometry and single-cell transcriptomes. Comparison of iPS-derived cells with patient-derived cells revealed altered chromatin accessibility at early and later bona fide leukemia stages, with aberrantly higher accessibility and expression of the osteogenic homeobox factor DLX3 that preceded increased accessibility to ETS factors. DLX3 overexpression in normal CD34+ cells increased accessibility to ETS motifs and reduced accessibility to GATA motifs. A DLX3 transcriptional module was globally enriched in both ETO2::GLIS2 AMKL and some aggressive pediatric osteosarcoma. Importantly, DLX3 knockout abrogated leukemia initiation in this ETO2::GLIS2 iPSC model. Collectively, the characterization of a novel human iPSC-derived AMKL model revealed that hijacking of the osteogenic homeobox transcription factor DLX3 is an essential early step in chromatin changes and leukemogenesis driven by the ETO2::GLIS2 fusion oncogene. The ETO2::GLIS2 fusion drives almost 20% of pediatric non–Down syndrome acute megakaryoblastic leukemia cases and is associated with a particularly poor outcome. Boudia and colleagues report a human induced pluripotent stem cell (iPSC) model of the disease, recapitulating the human disease and enabling a comprehensive molecular investigation. The authors identified osteogenic homeobox factor DLX3 as a critical player in the onset of leukemia and provide a system that could underpin future drug screening to generate novel treatment strategies.